Enhancing Students’ Science Learning Outcomes through Educaplay-Assisted Problem-Based Learning - Silvia Murni; Rahma Dewita; Rahmat Risky Hidayah; Vito Erwansyah; Lichia Rachmat (International Journal of Islamic Teaching and Learning, 2026)
This study was motivated by the suboptimal science learning process in which students tended to be passive, lacked participation in classroom activities, and experienced difficulties in answering varied practice questions, resulting in low learning outcomes. The study aimed to improve students’ science learning outcomes through Educaplay-assisted Problem-Based Learning. This study employed Classroom Action Research conducted in a third-grade class at an elementary school, Indonesia. The participants consisted of 15 students, including 6 male and 9 female students. Data were collected through observation, documentation, and tests, and analyzed using the stages of planning, action, observation, and reflection. The findings indicated a significant improvement in students’ learning outcomes across the research cycles. Students’ mastery learning increased from 26.67% in the pre-cycle to 53.33% in Cycle I, and further improved to 93.33% in Cycle II. The study concludes that Educaplay-assisted Problem-Based Learning effectively improves elementary students’ science learning outcomes and promotes more active participation in the learning process.